Preparation of sports activities with cultural perspective for Thailand's Green Marathon athletes - Pirapim Tangporm; Jakkawat Laphet; Karun Kidrakarn (Retos: Nuevas Tendencias en Educación Física, Deportes y Recreación)
Introduction: This study examines how sports and physical preparation influence athletes’ readiness, motivation, and eco-friendly behaviors in Thailand’s green marathon. it aims to investigate how consistent training, guided by self-determination theory, shapes environmental awareness and participation within the cultural context.